Lethargic Response to Aerosol Emissions in Current Climate Models. Issue 18 (19th September 2018) - Storelvmo, Trude; Heede, Ulla K.; Leirvik, Thomas; Phillips, Peter C. B.; Arndt, Philipp; Wild, Martin
Abstract: The global temperature trend observed over the last century is largely the result of two opposing effects—cooling from aerosol particles and greenhouse gas warming. While the effect of increasing greenhouse gas concentrations on Earth's radiation budget is well constrained, that due to anthropogenic aerosols is not, partly due to a lack of observations. However, long‐term surface measurements of changes in downward solar radiation (SDSR), an often used proxy for aerosol radiative impact, are available worldwide over the last half century. We compare SDSR changes from ∼1, 400 stations to those from the Coupled Model Intercomparison Project Version 5 global climate simulations over the period 1961–2005. The observed SDSR shows a strong early downward trend followed by a weaker trend reversal, broadly consistent with historical aerosol emissions. However, despite considerable changes to known aerosol emissions over time, the models show negligible SDSR trends, revealing a lethargic response to aerosol emissions and casting doubt on the accuracy of their future climate projections. Plain Language Summary: Observations of incoming solar radiation, as measured at approximately 1, 400 surface stations worldwide, show a strong downward trend from the 1960s to the 1980s, followed by a weaker trend reversal thereafter. These trends are thought to be due to changes in the amount of aerosol particles in the atmosphere, and we find support for that here in the temporal evolution of anthropogenic aerosol emissions. This is expected because aerosol particles reflect and/or absorb sunlight back to space and have a net cooling effect on Earth's climate. However, we find that the current generation of climate models simulates negligible solar radiation trends over the last half century, suggesting that they have underestimated the cooling effect that aerosol particles have had on climate in recent decades. Despite this, climate models tend to reproduce surface air temperature over the time period in question reasonably well. This, in turn, suggests that the models are not sensitive enough to increasing greenhouse gas concentrations in the atmosphere, with important implications for their ability to simulate future climate. Key Points: Trends in downward solar radiation measured at ∼1, 400 surface stations are presented for the last half century Historical aerosol emissions support the idea that these observed radiation trends were mainly due to changes in atmospheric aerosol loading CMIP5 simulations show negligible solar radiation trends over the same period, raising doubts about their ability to simulate future climate